2000
DOI: 10.1524/ract.2000.88.9-11.705
|View full text |Cite
|
Sign up to set email alerts
|

Sorption equilibrium and kinetics of NpO2+on dispersed particles of Na-montmorillonite

Abstract: NpO 2 + / Sorption / Na-montmorillonite / Affinity spectrum / Kinetic spectrum Summary. Sorption equilibrium and kinetics of NpO 2 + on dispersed particles of Na-montmorillonite were experimentally investigated by using a batch technique and a spectroscopic method, respectively. Considering the heterogeneity of sorption sites, we investigated the affinity spectra for the sorption of NpO 2 + . It was found that the spectrum for NpO 2 + was monomodal but asymmetrical and that the half-width at half-maximum of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Additionally, the solution chemistry of Np(V) can serve as a guide for that of Pu(V), whose instability towards disproportionation and reduction complicates experimental investigations. Many studies have investigated the behavior of Np(V) sorption onto clays, such as montmorillonite [25][26][27][28][29], smectite [30], bentonite [31], and Opalinus clay [32]. It has been found that the sorption of Np(V) depends on many parameters, such as pH value [27,31,32], Np(V) concentration [28,32], electrolyte concentration [33], and carbonate concentration [27,32].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the solution chemistry of Np(V) can serve as a guide for that of Pu(V), whose instability towards disproportionation and reduction complicates experimental investigations. Many studies have investigated the behavior of Np(V) sorption onto clays, such as montmorillonite [25][26][27][28][29], smectite [30], bentonite [31], and Opalinus clay [32]. It has been found that the sorption of Np(V) depends on many parameters, such as pH value [27,31,32], Np(V) concentration [28,32], electrolyte concentration [33], and carbonate concentration [27,32].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the sorption behaviour of Np(V) on different clay minerals, such as kaolinite [11,12], or smectite [13][14][15][16]. Sorption of Np(V) was found to depend on several factors, such as pH [11,13], Np concentration [11,14], partial pressure of CO 2 [11,13], and ionic strength [11].…”
Section: Introductionmentioning
confidence: 99%
“…Sorption of Np(V) was found to depend on several factors, such as pH [11,13], Np concentration [11,14], partial pressure of CO 2 [11,13], and ionic strength [11]. Only few studies on Np(V) sorption under higher partial pressures of CO 2 are reported.…”
Section: Introductionmentioning
confidence: 99%
“…This solid has been chosen because it could be a mineral representative of natural clay, which might be used as an engineered barrier thanks to its low permeability and its high sorption capacity. Up to now, many studies have been published on the retention properties of such a mineral, [27][28][29][30][31][32][33][34][35][36] but only a few have been devoted to a complete study combining both macroscopic and microscopic points of view.…”
Section: Introductionmentioning
confidence: 99%